2020
DOI: 10.1002/ange.201915685
|View full text |Cite
|
Sign up to set email alerts
|

The Biosynthesis of the Benzoxazole in Nataxazole Proceeds via an Unstable Ester and has Synthetic Utility

Abstract: Heterocycles, a class of molecules that includes oxazoles, constitute one of the most common building blocks in current pharmaceuticals and are common in medicinally important natural products. The antitumor natural product nataxazole is a model for a large class of benzoxazole‐containing molecules that are made by a pathway that is not characterized. We report structural, biochemical, and chemical evidence that benzoxazole biosynthesis proceeds through an ester generated by an ATP‐dependent adenylating enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 56 publications
(116 reference statements)
1
16
0
Order By: Relevance
“…In presence of MxcE, the areas of all detected amide and product peaks were increased. As expected from a previous study, [6] only NatL2 and NatAM were needed for the in vitro synthesis of the 3‐HBA‐derived benzoxazole ( 2 c ). Still, the presence of MxcE improved the production level of 2 c by 46 % (Table S3).…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…In presence of MxcE, the areas of all detected amide and product peaks were increased. As expected from a previous study, [6] only NatL2 and NatAM were needed for the in vitro synthesis of the 3‐HBA‐derived benzoxazole ( 2 c ). Still, the presence of MxcE improved the production level of 2 c by 46 % (Table S3).…”
Section: Resultssupporting
confidence: 61%
“…Previous studies indicated that only two enzymes are required for benzoxazole biosynthesis from 3‐HAA, namely an ATP‐dependent ligase and an amidohydrolase [6] . The two genes natL2 and natAM from the nataxazole biosynthetic gene cluster of Streptomyces sp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose, benzoxazole derivatives have attracted a lot of attention in recent years based on their usage as intermediates in the creation of novel biological materials. The compounds having the presence of benzoxazole skeleton in synthetically important and naturally occurring molecules that possess anti-inflammatory [4][5] and anticancer activity [6][7][8][9][10][11][12] are displayed in Figure 1.…”
Section: Introductionmentioning
confidence: 99%